Exploration of Major Trends in the Realm of Native American Fiction: The Impact of Native American Novels on Literature and Identity Formation (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Native American novels are primarily associated with representation of Indianness, culture, traditions, mythology, reservation, story-telling, identity and mixed blood and community. N. Scott Momaday’s world famous novel entitled “House Made of Dawn (1968) created a revolution in the history of Native American literature by achieving the Pulitzer prize in 1969 and ushering an era of Renaissance. It was prominent critic Kenneth Lincoln who used the term Native American Renaissance on account of remarkable contribution of N. Scott Momaday, James Welch, Gerald Vizenor, Leslie Marmon Silko, Simon Ortiz, Louise Erdrich and Paula Gunn Allen in the development of Native American fiction.